Pseudaeginella makranensis sp. nov., a new species of caprellid (Crustacea: Amphipoda) from the Iranian coasts of Gulf of Oman - Momtazi, Farzaneh; Khalaji-Pirbalouty, Valiallah; Golestaninasab, Mehdi (Zootaxa, 2023)
Pseudaeginella makranensis sp. nov. is described from the Iranian coast of the Oman Sea. This species differs from other Pseudaeginella species by setose antennae, setae arrangement on mandibular palp, basis of male gnathopod 2 larger than pereonite 2, and bearing subrectangular propodus in second male gnathopod. A key to all species of Pseudaeginella Mayer, 1890 is provided.